ANALISIS PENGARUH CURRENT RATIO, CASH RATIO, DAN QUICK RATIO TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Ardiansyah Ardiansyah; Nur Azizah Anabas (Taksasila Edukasi Insani, 2023)
The purpose of this study is to determine the effect of the Current Ratio, Cash Ratio, and Quick Ratio on profit growth in sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The type of research used is associative research. The population used in this study amounted to 54 companies and the sampling technique used in this study was purposive sampling technique. Based on predetermined sample selection criteria, a total sample of 45 companies was obtained. Data analysis using multiple linear regression analysis.Simultaneous test results using the F test is 0.410 0.05. These results indicate that the three independent variables namely Current Ratio, Cash Ratio, and Quick Ratio together do not have a significant effect on profit growth. Whereas the partial test using the t test shows that the Current Ratio, Cash Ratio, and Quick Ratio do not have a significant effect on profit growth as evidenced by the t-count Current Ratio of 0.670 the t-table value of 2.022, the t-value of Cash Ratio is -1.546 t table value of 2.022, and the t value of Quick Ratio is -0.077 t table value of 2.022. The results of the coefficient of determination obtained R Square of 0.072, indicating that the influence of the variables Current Ratio, Cash Ratio, and Quick Ratio is 7.2% while the remaining 92.8% is influenced by other variables not examined in this study. Keywords : Current ratio; Cash ratio; Quick ratio; Profite growth.